Choroidal Thickness Changes During the Menstrual Cycle. (November 2013) - Ulaş, Fatih; Doğan, Ümit; Duran, Bülent; Keleş, Asena; Ağca, Sümeyra; Çelebi, Serdal
Abstract Purpose: To evaluate the effects of the menstrual cycle on the choroidal thickness of healthy women of reproductive age using spectral-domain optical coherence tomography. Materials and methods: A total of 23 right eyes of 23 women with regular natural menstrual cycles of 28–30 d and ages 22–30 years were included in this prospective study. The choroidal thicknesses of the women were measured using high-resolution spectral-domain optical coherence tomography line scans with the activated enhanced depth imaging mode in the early follicular, ovulatory and mid-luteal phases of the menstrual cycle (3rd, 14th and 21st days) using a follow-up scanning protocol of the Spectralis optical coherence tomograph by setting the early follicular phase scan as the reference image. Choroidal thickness measurements were taken at the fovea and at two points that were 1500 µm nasal and temporal to the fovea. The mean arterial pressure, spherical equivalent, intraocular pressure, central corneal thickness and retinal and retinal nerve fiber layer thicknesses were also measured. All measurements were taken within the same menstrual cycle. Results: The mean ± standard deviation (standard error of the mean) of subfoveal choroidal thicknesses in the early follicular, ovulatory and mid-luteal phases were 383.87 ± 84.38 (17.59), 373.74 ± 82.40 (17.18) and 359.09 ± 79.65 (16.61) µm, respectively. The relative reductions in choroidal thickness between early follicular and ovulatory phases and early follicular and mid-luteal phases were 2.64% and 6.47%, respectively. The subfoveal choroidal thickness was decreased significantly in the mid-luteal phase when compared with both the early follicular (p < 0.001) and ovulatory phases (p = 0.003). However, the measures of subfoveal choroidal thickness in the early follicular phase were non-conclusively greater (p = 0.071) than in the ovulatory phase. Additionally, the mean arterial pressure, spherical equivalent, intraocular pressure, central corneal thickness and retinal and retinal nerve fiber layer thicknesses did not significantly differ during the menstrual cycle (p > 0.05 for all). Conclusions: The choroidal thickness decreased significantly in the mid-luteal phase of the menstrual cycle in young, healthy women. These findings emphasize the importance of the menstrual phase in the interpretation of choroidal thickness measurements in women of reproductive age.